2009
DOI: 10.1021/jp903818q
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Characterization of CuFe2O4 and Cu/Fe3O4 Water−Gas Shift Catalysts

Abstract: Mixtures of copper and iron oxides are used as industrial catalysts for the water-gas shift (WGS, CO + H 2 O f H 2 + CO 2 ). In-situ time-resolved X-ray diffraction, X-ray absorption fine structure, and atomic pair distribution function analysis were used to study the reduction of CuFe 2 O 4 with CO and the behavior of CuFe 2 O 4 and Cu/Fe 2 O 3 catalysts under WGS reaction conditions. MetalToxygenTmetal interactions enhance the stability of Cu 2+ and Fe 3+ in the CuFe 2 O 4 lattice, and the mixed-metal oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 54 publications
6
117
0
Order By: Relevance
“…Similar trends were also reported in this literature [17], [46], [110]. Reduction of Cu +1 to Cu is more difficult than Cu +2 to Cu [69], [111]. This rise in current density was due to the stability of Cu +1 with the support of CNT.…”
Section: Sem and Edx Analysissupporting
confidence: 87%
“…Similar trends were also reported in this literature [17], [46], [110]. Reduction of Cu +1 to Cu is more difficult than Cu +2 to Cu [69], [111]. This rise in current density was due to the stability of Cu +1 with the support of CNT.…”
Section: Sem and Edx Analysissupporting
confidence: 87%
“…The reduction of Pd oxide was easy and occurred in the lower temperature, and the generated metallic Pd further activated hydrogen and promoted the reduction of other oxides. However, the weak diffraction peaks ascribed to CuFe 2 O 4 in the Pd-loaded samples after reduction could still be identified even under the promoted reduction effect of Pd due to the difficult reduction of CuFe 2 O 4 [16]. It has been reported that the undissociative activation of CO occurs on the sites of metal ions and metallic Cu while the dissociation of CO to C* and O* species mainly happens on the metallic sites of Fe and Co [10,17,18].…”
Section: Catalytic Testsmentioning
confidence: 96%
“…The partially reduced magnetite phase might be carburized more easily under Fischer-Tropsch conditions, thus enhancing the activity of promoted iron-based catalyst. The enhanced rate of carburization would be associated with an increased CO 2 -selectivity [13,23].…”
Section: Introductionmentioning
confidence: 99%